P3.229 Prevalence and Correlates of Mycoplasma Genitalium in HIV-Positive African Women. (13th July 2013) - Sawadogo, B; Muzah, B; Gilham, C; Djigma, F; Maseko, V; Kelly, H; Simpore, J; Lewis, D; Segondy, M; Mayaud, P
Abstract : Background: To assess the prevalence of Mycoplasma genitalium (MG) among HIV-positive African women and its associations with cervical infections and disease, other STI signs and CD4+ counts. Methods: The HARP study aims to evaluate cervical cancer screening tests among HIV-positive women aged 25–50 in Burkina Faso (BF) and South Africa (SA). In addition, real time PCR assays were used to detect Neisseria gonorrhoeae (NG), Chlamydia trachomatis (CT), Trichomonas vaginalis (TV), and MG, using Sacace RT-PCRs in BF, and multiplex PCR followed by confirmatory APTIMA ® assays for NG/CT and Sacace RT-PCR for TV/MG in SA. HPV genotyping was performed using Digene ® HC2 assay. Results: 628 women were enrolled in BF and 624 in SA, two-thirds of whom were on antiretroviral therapy. The distribution of CD4+ count (cells/µL) was similar in both sites: 68% with CD4+ ≥ 350 and 10% with CD4+ < 200. Prevalence of MG was similar in both populations: 7.1% in BF (41/575) and 7.6% (47/622) in SA, and, overall, 6.7%, 8.2% and 10.1% among women with CD4+ ≥ 350, 200–349 and < 200, respectively (Table). MG was detected in 8.2% of high-risk (HR)-HPV-positive women vs. 3.9% of women without HR-HPV (P = 0.005), and in 7.7% of women with low-grade cervical intraepithelial lesions (LSIL), and 10.0% of women with high-grade lesions (HSIL+) and above vs. 6.2% in women without lesions (P-trend = 0.095). Co-infection with NG, CT, TV and BV was observed in 0%, 11.4%, 11.4% and 9.0% respectively. In multivariate analysis (Table), MG correlated negatively with age (P-trend = 0.003) and clinical PID (aOR = 0.29, P = 0.05), and positively with T vaginalis (aOR = 1.7, P = 0.06) but not with any other particular STI infection or syndrome; and tended to increase with decreasing CD4+ count (P = 0.13). Conclusions: MG prevalence is relatively high among these HIV-positive African women and is associated with younger age, trichomoniasis and marginally with CD4. Table. Multivariate analysis showing factors originally associated in univariate analysis with Mycoplasma genitalium in Burkina Faso and South Africa